Knowledge Regarding Antibiotic Use, its Resistance and Consequences among Higher Secondary Students in Private Schools of Kathmandu Valley - Deo, Satish K; Gautam, Naveen; Gyawali, Siddinath; Shrestha, Deepti; Yadav, Shikha (Journal of Institute of Medicine Nepal, 2019)
Introduction The lack of awareness on the appropriate use of antibiotics, its dose and duration is one of the leading causes of global antimicrobial resistance (AMR). AMR poses a growing threat to public health, as infections from resistant strains of microbes become increasingly difficult to treat, resulting in prolonged illness and greater risk of death. Hence, this study would be an important reference for determining the scope of the problem which will be essential for formulating and monitoring an effective response to antibiotic use and its problem of resistance. Methods A descriptive cross-sectional study was done among higher secondary level students from selected schools in Kathmandu valley. Baseline data was collected after a tutorial session through semi-structured questionnaires which was based on past researches and verified using expert consultation. Ethical consideration was maintained throughout the study. Descriptive statistics was used to find out the KAP level including knowledge score and attitude-practice score of the selected population. Results Among 465 participants conducted in our research, the overall average knowledge score of the participants was found to be 73.3% while the attitude-practice score was 60.53%. It was found that 80.86% of the participants had heard the term “antibiotic resistance”. The knowledge score percentage among the students of grade 10 and 11 had no significant difference (p value= 0.592). Conclusion Our study concludes that if topics like antibiotics and their judicial use is well covered in school curriculum, it can produce measurable change in knowledge, attitude and practice level of the students.